Personal Values, Means End-Chain, Identity and Consumption Behavior in Foods: A Bibliometric Review - Castro, Álvaro Leonel de Oliveira (2018)
Objective: In the context of food consumption, from the standpoint of theories of personal values, means-end chain and identity formation, this article aimed at the bibliographic indexes in the area of ​​research, covering the main authors and periodicals that publish and are cited, as references that are used, such as search terms, as well as the frequency of publication by year and countries.Method: Articles related to the topic were searched in the academic bases Web of Science and SCOPUS, which returned in 85 manuscripts. These were organized in the mentions manager of My Endnote Web, for further analysis, using Excel spreadsheets and using CiteSpace 5.1.R3 software.Originality/Relevance: The analyzed theories have relevance in the studies on the behavior of consumption in food. However, these concepts could be worked together, resulting in a new possibility of understanding the motivations intrinsic to the individual in acts of consumption.Results: It is noticeable that the discussion on the subject has been growing since 2011, with higher index of publication in European journals, by researchers from Europe, North America and Australians. The journals that publish are the most cited, with authors relevant to theoretical references and empirical research.Theoretical/methodological contributions: This bibliometric review points to a gap in the relationship between these three theoretical perspectives, so that the combination of these concepts could enable the extraction of identity traits from personal values, with the means-end chain being a possible mediating link.